A review of the tourist industry's role in Indonesia's GDP growth - Johanes, Riky; Takari, Dedi; Sabirin, Sabirin (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2024)
This research was conducted to know the development of the tourism sector in Indonesia in recent years and to find out how much the tourism sector contributes to national income in Indonesia. The type of research used in this research is quantitative descriptive. The kind of data used in this research is secondary data. The secondary data is recorded systematically in the form of time series data. This research used data on the number of domestic tourist visits, the number of foreign visits, and the tourism sector's contribution to Indonesia's GDP from 1999-2022. Data sources are a means of finding the required data. Data from official publications is obtained based on information compiled and published by certain agencies, namely the Central Statistics Agency (BPS) and other agencies. The findings in this research are that state revenues from the tourism sector are starting to improve as the pandemic ends. Several travel restrictions have begun to be removed so that the tourism sector has already started to provide income for the country through all its economic activities. The tourism sector's contribution to the Indonesian economy is still minimal. In the last 3 years, tourism has contributed no more than 2% of Indonesia's total Gross Domestic Product.